Multijunction photovoltaic device with metal oxynitride layer

CN115777150BActive Publication Date: 2026-10-30OXFORD PHOTOVOLTAICS LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180042326.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-18
Filing Date
2021-06-17
Publication Date
2026-10-30
Estimated Expiration
2041-06-17

AI Technical Summary

Technical Problem

此外,在这种特定机制下相对较高的腔室压力与较高的气体离解率相结合会导致在工艺过程中发生等离子体聚合,从而对工艺稳定性和可重复性产生负面影响

Benefits of technology

[0011]本发明通过如本文所定义的权利要求的主题减轻了这些缺点。将在下面的部分中对本发明的其他优点进行进一步详细说明。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115777150B_ABST
    Figure CN115777150B_ABST
Patent Text Reader

Abstract

A multi-junction photovoltaic device is disclosed comprising a metal nitride oxide layer between a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material. Furthermore, a method of manufacturing said multi-junction photovoltaic device is also disclosed. The metal nitride oxide is preferably titanium nitride oxide. Advantageously, the device can be produced in a simple, fast, consistent and inexpensive manner, while the properties of the titanium nitride oxide layer can be adjusted to avoid the appearance of local shunt paths and reduce reflection losses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to photovoltaic (PV) devices, particularly multi-junction photovoltaic devices, such as tandem solar cells and PV panels, and to methods for manufacturing them. Background Technology

[0002] Solar energy conversion is one of the most promising technologies for providing renewable energy. However, reducing the cost of manufacturing equipment for effectively capturing solar energy, particularly the cost of materials and necessary equipment, remains crucial for promoting its widespread use.

[0003] Single-junction solar cells—such as those made of silicon pn junctions—have a maximum theoretical efficiency of about 29% and a practical efficiency of up to 26% under AM1.5G conditions (see, for example, "Photovoltaic Solar Energy – from Fundamentals to Applications," edited by A. Reinders et al., Wiley ISBN 9781118927465

[2017] , p. 164). However, if cells with materials having higher band gaps are stacked on top of silicon single-junction cells (or other types of single-junction cells) and connected in series, the limiting theoretical efficiency increases to over 40%. Therefore, series and other multi-junction cell technologies are currently receiving increasing attention.

[0004] A particularly promising class of monolithic tandem or multijunction photovoltaic (PV) solar cells will include a perovskite (e.g., organometal halide perovskite) sub-cell combined with a second sub-cell that may include, for example, a photoactive silicon absorber. Perovskites are known in the art to be ideal light absorbers in PV devices because they exhibit favorable band gaps, high absorption coefficients, and long diffusion lengths.

[0005] Conventional perovskite / silicon tandem solar cells contain a transparent conductive oxide (TCO) layer (enclosed on top of the silicon bottom sub-cell) that is necessary to form a low-ohmic tunnel recombination contact between the silicon and perovskite sub-cells. Typical examples of TCO materials include indium tin oxide (ITO) or zinc oxide (AZO, GZO, or IZO) doped with aluminum, gallium, or indium, with ITO being the most commonly used.

[0006] However, using interconnect layers including ITO can be disadvantageous for several reasons. First, ITO layers tend to form highly reflective interfaces due to their unfavorable refractive index order. Furthermore, they exhibit high lateral conductivity, which can lead to bypass paths through the perovskite absorber in the finished device.

[0007] To reduce reflection between the perovskite top cell and the silicon bottom cell, L. Mazzarella et al., Advanced Energy Materials 2019, 9(14), 1803241 proposed using substoichiometric nanocrystalline silicon oxide (nc-SiO2) located on top of the amorphous silicon i-layer and below the ITO layer. x The layer is a p-layer that makes contact with the p-layer of the top battery.

[0008] WO 2018 / 150203 A1 further discloses an intermediate region comprising an interconnect layer between a perovskite-based sub-cell and a photoactive silicon-based sub-cell. The interconnect layer has a two-phase material comprising elongated silicon nanocrystals embedded in a silicon oxide matrix, which can reduce the adverse effects of local bypass paths and can be tuned to reduce reflection loss.

[0009] However, the process used for depositing two-phase materials in WO 2018 / 150203 A1 is a special type of plasma-enhanced chemical vapor deposition (PECVD), which relies on the interaction of multiple surface chemical mechanisms (such as preferential etching, large surface diffusion, and chemical annealing) to achieve structures with desired lateral and longitudinal electrical conductivity, all of which correspondingly result in a relatively low deposition rate of approximately 0.2 nm / s. Furthermore, the relatively high chamber pressure combined with a high gas dissociation rate under this specific mechanism leads to plasma polymerization during the process, negatively impacting process stability and repeatability. Overall, PECVD processes also require expensive and sophisticated equipment.

[0010] Given the above, it is still desirable to provide multi-junction photovoltaic devices that overcome the aforementioned drawbacks of known interconnect layers and can be produced simultaneously in a simpler, faster, more consistent, and cheaper manner. Summary of the Invention

[0011] The present invention mitigates these disadvantages through the subject matter of the claims as defined herein. Further advantages of the invention will be described in detail in the following sections.

[0012] According to a first aspect, the present invention relates to a multi-junction photovoltaic device comprising a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material, characterized in that a metal nitride (M) is disposed between the first sub-cell and the second sub-cell. n O x N yUnlike nanocrystalline silicon oxide, metal oxynitrides, such as titanium oxynitride, can be deposited at a higher deposition rate via physical vapor deposition (e.g., sputtering). The refractive index of the resulting layer can be easily adjusted to the desired level, thereby reducing reflectivity loss and significantly improving the layer absorption rate of the bottom sub-cell. Simultaneously, the metal (e.g., titanium) oxynitride layer is transparent to infrared light and exhibits excellent electrical conductivity for the effective electrical interconnection of the two sub-cells.

[0013] A second aspect of the invention relates to a method of manufacturing a multi-junction photovoltaic device, the multi-junction photovoltaic device comprising a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material, the method comprising the step of depositing a metal nitride layer between the first sub-cell and the second sub-cell.

[0014] Preferred embodiments of the multi-junction photovoltaic device according to the present invention, its manufacturing method, and other aspects of the invention are described in the following specification and claims. Attached Figure Description

[0015] Embodiments of the present invention will now be described by way of example only, with reference to the accompanying schematic diagrams, wherein:

[0016] Figure 1 An example of a monolithically integrated multi-junction photovoltaic device according to the present invention is illustrated schematically.

[0017] Figure 2 A specific example of a monolithically integrated multi-junction photovoltaic device with an inverted structure according to the present invention is shown.

[0018] Figure 3 Another specific example of a monolithically integrated multi-junction photovoltaic device with a conventional structure according to the present invention is shown.

[0019] Figure 4 The power conversion efficiency (PCE) and short-circuit current density (J / L) of the six series-connected cells are shown. SC ), open circuit voltage (V) OC ) and fill factor (FF), wherein the three series cells have no sandwich separation and the three series cells have TiO x N y Mezzanine separation. For each of the four parameters listed above, the results are normalized to the average value without mezzanine separation.

[0020] Figure 5 The diagram shows the relationship between measured external quantum efficiency (EQE) and wavelength (in nm) from two representative tandem cells, one from a cell without a sandwich separator and the other from a TiO₂ cell. x N ySandwich separation. The perovskite top cell absorbs in the 300-780nm range, while the silicon bottom cell absorbs in the 500-1200nm range.

[0021] Figure 6 It shows the way Figure 5 The ones used for those without sandwich layers and those with TiO x N y J values ​​of perovskite sub-cells and silicon sub-cells calculated using EQE curves of sandwich structures. SC Box plot.

[0022] Figure 7 The image shows the absence of a sandwich partition (left) and the presence of TiO2. x N y An example of a multi-junction photovoltaic cell stack with a sandwich partition (right).

[0023] Figure 8 The diagram shows the case without the interlayer separator 1 (top) and with TiO2. x N y Current density J in case of sandwich partition 2 (bottom) SC The voltage characteristics of the separation.

[0024] Figure 9 A graph showing the refractive index (including absorption or extinction coefficient, "nk") versus wavelength, measured by spectroelastic photometry, is presented to demonstrate a series of TiO₂ deposits under different gas flow rates of 0 standard cubic centimeters (sccm), 40 sccm, and 80 sccm. x N y Optical properties of thin films.

[0025] Figure 10 It shows no interlayer separator (top) and has TiO2. x N y Results of optical simulations of the sandwich partition (bottom), showing the absorption of each simulated EQE for the layers in the simulated stack. The legend on the right side of the spectrum corresponds to the tandem cell layers and their respective components.

[0026] Figure 11 Various TiO2 types are shown. x N y Simulation of the bottom sub-cell of sandwich, nc-Si reference (baseline), and nc-SiOx reference J SC value. Detailed Implementation

[0027] To gain a more complete understanding of the invention, reference is now made to the following description of its illustrative embodiments:

[0028] Multijunction photovoltaic equipment

[0029] In a first embodiment, the present invention relates to a multi-junction photovoltaic device comprising a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material, characterized in that a metal (e.g., titanium) oxynitride layer is disposed between the first and second sub-cells. "Multi-junction" refers to two or more. Preferably, the second sub-cell is a silicon sub-cell. Advantageously, the photovoltaic device has a monolithically integrated structure, such as a series structure, comprising the first and second sub-cells. In a monolithically integrated multi-junction photovoltaic device, two or more photovoltaic sub-cells are deposited directly on top of each other and are thus electrically connected in series. The photovoltaic device may optionally also include an intermediate region connecting the first sub-cell to the second sub-cell, wherein each intermediate region comprises one or more conductive interconnect layers.

[0030] Figure 1 An exemplary overall structure of a photovoltaic device according to the present invention is shown. The monolithic multi-junction photovoltaic device (100) shown includes a top perovskite-based sub-cell serving as a first sub-cell (110) between a front electrode (101) and a rear electrode (102), and a bottom second sub-cell (120), wherein a metal (e.g., titanium) oxide nitride layer (103) is disposed between the first sub-cell (110) and the second sub-cell (120). This layer is represented in the figure by the molecular formula MO. x N y It can be represented as MnO, but it can also be used. x N y This indicates that an additional layer may be provided between the first and second sub-cells.

[0031] As used herein, the term "front electrode" refers to an electrode disposed on the side or surface of a photovoltaic device that is intended to be exposed to sunlight. Therefore, the front electrode typically needs to be transparent or translucent to allow light to pass through the electrode and reach the photoactive layer disposed beneath it. Similarly, as used herein, the term "rear electrode" refers to an electrode disposed on the side or surface of a photovoltaic device opposite to the side or surface intended to be exposed to sunlight. The selection of the front and rear electrodes of the optoelectronic device of the present invention can be suitably chosen by those skilled in the art from materials known in the art and can depend on the type of structure. Exemplary materials include, but are not limited to, metals and metal oxides such as tin oxide, ITO (indium tin oxide), FTO (fluorine-doped tin oxide), or AZO (aluminum-doped tin oxide), and high work function metals such as aluminum, gold, silver, nickel, palladium, or platinum. The thickness of the front and rear electrodes can be suitably chosen by those skilled in the art and is typically in the range of 50 nm to 600 nm, more typically in the range of 300 nm to 500 nm. For example, the thickness can be 400 nm. The first electrode is typically disposed on a glass substrate.

[0032] As used herein, the term "perovskite" refers to a material having a structure associated with that of CaTiO3. The structure of CaTiO3 can be represented by the molecular formula ABX3, where A and B represent cations of different sizes, and X is an anion. In the unit cell, the A cation is located at (0, 0, 0), the B cation at (1 / 2, 1 / 2, 1 / 2), and the X anion at (1 / 2, 1 / 2, 0). The A cation is typically larger than the B cation. Those skilled in the art will understand that A, B, and X can be varied to twist the structure of the perovskite material from that of CaTiO3 to a twisted structure with lower symmetry. The symmetry is also reduced if the material includes layers with a structure associated with that of CaTiO3. Those skilled in the art will understand that perovskite materials can be represented by the molecular formula [A][B][X]3, where [A] is at least one cation, [B] is at least one cation, and [X] is at least one anion. When a perovskite includes more than one A cation, the different A cations can be distributed at the A sites in an ordered or disordered manner. When a perovskite includes more than one B cation, the different B cations can be distributed at the B sites in an ordered or disordered manner. When a perovskite includes more than one X anion, the different X ions can be distributed at the X sites in an ordered or disordered manner. The symmetry of perovskites containing more than one A cation, more than one B cation, or more than one X cation is generally lower than that of CaTiO3.

[0033] Generally, as used herein, the term "perovskite" refers to (a) a material having a three-dimensional crystal structure associated with the structure of CaTiO3 or (b) a material comprising layers having a structure associated with the structure of CaTiO3. While both types of perovskites can be used in the apparatus according to the invention, the first type of perovskite (a), i.e., perovskites with a three-dimensional (3D) crystal structure, is preferred. Such perovskites typically comprise a 3D network of perovskite cells with no separation between layers. On the other hand, the second type of perovskite (b) comprises perovskites with a two-dimensional (2D) layered structure. Perovskites with a 2D layered structure may comprise perovskite cell layers separated by (inserted) molecules; an example of such a 2D layered perovskite is [2-(1-cyclohexenyl)ethylammonium]2PbBr4. 2D layered perovskites tend to have higher exciton binding energies, which favor the generation of bound electron-hole pairs (excitons) rather than free charge carriers under photoexcitation. Bound electron / hole pairs may not be able to move sufficiently to the p-type or n-type contacts, where they can transfer (ionize) and generate free charges. Therefore, to generate free charges, the exciton binding energy must be overcome, which represents the energy cost of the charge generation process and leads to lower voltage and lower efficiency in photovoltaic cells. In contrast, perovskites with a 3D crystal structure tend to have much lower exciton binding energies (in thermal terms) and thus can generate free carriers directly after photoexcitation. Therefore, the perovskite semiconductor used in the apparatus and method of the present invention is preferably a perovskite with a three-dimensional crystal structure.

[0034] In a preferred embodiment, the perovskite material has the general formula [A][B][X]3, wherein [A] is one or more monovalent cations, [B] is one or more divalent inorganic cations, and [X] is one or more halide anions, preferably selected from fluorides, chlorides, bromides, and iodides, and more preferably selected from chlorides, bromides, and iodides. More preferably, [X] includes one or more halide anions selected from bromides and iodides. [A] preferably includes one or more halide anions selected from methylammonium (CH3NH3). + ), formamidin (HC(NH)2)2 + ) and ethylammonium (CH3CH2NH3) + The organic cation is selected from methylammonium (CH3NH3). + ) and formamidin (HC(NH)2)2 + [A] may include one or more organic cations selected from Cs. + 、Rb + Cu + Pd + Pt + Ag+ Au + ,Rh + and Ru + [B] Preferably includes at least one inorganic cation selected from Pb. 2+ and Sn 2+ The divalent inorganic cation, and preferably including Pb 2+ Further examples of preferred perovskite materials are disclosed, for example, in the following literature: Kojima, A. et al., Journal of the American Chemical Society 2009, 131(17), pp. 6050-1; Zuo, C. et al., Adv. Sci. 2016, 3, 1500324; WO 2013 / 171517 A1; WO 2014 / 045021 A1; WO 2016 / 198898A1 and WO 2018 / 15203A1.

[0035] As used herein, the term "perovskite light absorber material" refers to a perovskite material capable of absorbing light and thereby generating free charge carriers. However, a perovskite material can also be a perovskite material capable of emitting light by accepting charges (electrons and holes), which then recombine to emit light.

[0036] Those skilled in the art will understand that the perovskite material used in this invention can be a perovskite that acts as an n-type electron transport semiconductor when photo-doped. Alternatively, it can be a perovskite that acts as a p-type hole transport semiconductor when photo-doped. Therefore, the perovskite can be n-type or p-type, or it can be an intrinsic semiconductor. In a preferred embodiment, the perovskite used is a perovskite that acts as an n-type electron transport semiconductor when photo-doped. Perovskite materials can exhibit bipolar charge transport and thus act as both n-type and p-type semiconductors. Specifically, the perovskite can act as an n-type or p-type semiconductor depending on the type of junction formed between the perovskite and adjacent materials. Typically, the perovskite semiconductor used in this invention is a photosensitive material, i.e., a material capable of both photogeneration and charge transport.

[0037] The term "metal nitride" as used in this article refers to metals with the molecular formula M n O x N y The materials, x and y, and the concentration ratio x / y (expressed as the ratio of the atomic percentages between oxygen concentration x and nitrogen concentration y, also known as the O / N ratio) can be appropriately adjusted to balance the desired electrical conductivity, light transmittance, and reflectance of the metal nitride layer, depending on the deposition thickness of the layer. Metal M is preferably an early transition metal, such as metals from groups 4-6 of the periodic table. Early transition nitride metals (M...) are known... n Ox N y This will form non-stoichiometric interstitial compounds with high free carrier concentrations. The preferred molecular formula for metal nitrides is M. n O x N y Where n is 1 or 2. The advantages of metal nitrides over their corresponding oxides include simple fabrication methods (both can be deposited by sputtering) and the introduction of N allowing for optimized refractive index (RI). These features make these materials well-suited for sandwich applications in multi-junction photovoltaic devices. The ability to fine-tune the system facilitates achieving maximum efficiency.

[0038] Preferred metals for metal nitrides are Ti, W, Mo, Hf, Ta, Nb, Zr, Cr, and V, which form the following nitrides: Ti n O x N y W n O x N y Mo n O x N y Hf n O x N y Ta n O x N y 、Nb n O x N y Zr n O x N y Cr n O x N y V n O x N y The reference oxidation states (RIs) of the corresponding metal oxides for these nitrogen oxides are shown in the table below. The RIs can then be further fine-tuned using N to suit the present invention. The oxides given in the table are merely exemplary and the present invention is not limited to these.

[0039]

[0040]

[0041] Table 1: The RI ranges listed in the table above are provided to cover the different values ​​in the references (see TiO2, WO3, MoO3), or because they are approximations extracted from the figures in the references.

[0042] As shown in the table above, the range of metal oxides is approximately 1.8-2.5. These can be further adjusted by the amount of nitrogen content to make them suitable for the present invention, wherein the preferred refractive index of the metal nitride is between 2.39 and 2.9.

[0043] The preferred metal is titanium. As used herein, the term "titanium oxynitride" refers to titanium oxide with the molecular formula TiO2. x N y The materials, x and y, and the concentration ratio x / y (expressed as the ratio of atomic percentages between nitrogen concentration x and oxygen concentration y, also known as the O / N ratio) can be appropriately adjusted to balance the desired electrical conductivity, light transmittance, and reflectance of the titanium oxynitride layer, depending on the deposition thickness of the layer. From this perspective, x is preferably in the range of 0.60 to 0.95, and y is in the range of 0.10 to 1.2. Furthermore, or alternatively, an x / y ratio in the range of 0.4 to 5 may be preferred, and an x / y ratio in the range of 0.6 to 4.5 is particularly preferred. As will be explained below in conjunction with the second embodiment, the O / N ratio and the properties of the TiOxNy film can be controlled directly by appropriately adjusting the deposition conditions. As mentioned above, the deposition of the titanium oxynitride layer can be performed by a physical vapor deposition (PVD) method (e.g., sputtering), thus requiring less complex equipment and allowing for higher deposition rates compared to PECVD methods used to prepare known interconnect layers.

[0044] Typically, it is preferred that the refractive index n of the metallic (e.g., titanium) oxynitride layer is between that of the perovskite material layer and the material upon which the second sub-cell is based. Furthermore, if an additional intermediate layer is used between the first and second sub-cells, it is preferable that the refractive index of each layer is increased in the direction of the optical path to minimize reflectivity loss. In a preferred embodiment, the titanium oxynitride layer is suitable to have a refractive index n in the range of 2.3 to 3.7, more preferably in the range of 2.3 to 3.2, and particularly preferably between 2.3 and 2.9, for example, 2.4 to 2.8, given values ​​typically measured relative to light with a wavelength of 600 nm. In a preferred embodiment, the thickness of the titanium oxynitride layer is between 15 nm and 300 nm, more preferably between 20 nm and 200 nm, and particularly preferably between 40 nm and 160 nm. By adjusting the optical thickness and refractive index of the titanium oxynitride layer according to the above ranges, reflectivity can be effectively reduced.

[0045] In a preferred embodiment of the present invention, the first sub-cell further includes an n-type semiconductor layer and a p-type semiconductor layer, wherein the n-type semiconductor layer is on one surface of the layer comprising the perovskite light absorber material, and the p-type semiconductor layer is on the other surface of the layer comprising the perovskite light absorber material (i.e., the surface opposite to the n-type semiconductor layer).

[0046] As used herein, the term "n-type" refers to a region, layer, or material comprising an intrinsic semiconductor with an electron concentration greater than the hole concentration. Similarly, the term "n-type semiconductor layer" refers to a layer of electron transport (i.e., n-type) semiconductor material. The material may be a single electron transport semiconductor compound or element, or a mixture of two or more electron transport semiconductor compounds or elements. The electron transport semiconductor compound or element may be undoped or doped with one or more dopant elements. While not limited thereto, examples of n-type semiconductor materials include, for example, inorganic materials selected from: oxides of titanium, tin, zinc, niobium, tantalum, tungsten, indium, gallium, neodymium, palladium, cadmium, or oxides of two or more of these metals; sulfides of cadmium, tin, copper, zinc, or sulfides of two or more of these metals; selenides of cadmium, zinc, indium, gallium, or selenides of two or more of these metals; or tellurides of cadmium, zinc, cadmium, or tin, or tellurides of two or more of these metals. Other examples include organic and polymeric electron transport materials and electrolytes, such as fullerenes or fullerene derivatives, organic electron transport materials including perylene or its derivatives, or poly{[N,NO-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alternating-5,50-(2,20-bithiophene)}(P(NDI2OD-T2)).

[0047] As used herein, the term "p-type" refers to a region, layer, or material comprising an intrinsic semiconductor with a hole concentration greater than an electron concentration. The term "p-type semiconductor layer" refers to a layer of hole-transporting (i.e., p-type) semiconductor material. The hole-transporting (i.e., p-type) semiconductor material can be a single hole-transporting semiconductor compound or element, or a mixture of two or more hole-transporting semiconductor compounds or elements. The hole-transporting semiconductor compound or element may be undoped or doped with one or more dopant elements. The p-type layer used in the optoelectronic device of this invention may comprise inorganic or organic p-type materials.Although not limited to this, examples of p-type semiconductor materials include polymeric or molecular hole transporters (e.g., spiro-OMeTAD(2,2',7,7'-tetra-(N,N-di-p-methoxyaniline)9,9′-spirodifluorene)), P3HT (poly(3-hexylthiophene)), PCPDTBT (poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopentane[2,1-b:3,4-b']dithiophene-2,6-diyl]]), PVK (poly(N-vinylcarbazole)), and HTM-TFSI (1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imidazolium)). Amines), Li-TFSI (lithium bis(trifluoromethanesulfonyl)imide) or tBP (tert-butylpyridine); molecular hole transport compounds, polymer hole transport compounds and copolymer hole transport compounds (e.g. polymers or copolymers comprising one or more of the following moieties: phenylthio, phenylene, dithiazolyl, benzothiazolyl, diketopyrrolopyrrole, ethoxydithiophene, amino, triphenylamino, carbazole, ethylenedioxothiophene, dioxothiophene or fluorene); m-MTDATA (4,4′,4″-tris(methylphenylphenylamino)triphenylamine), MeOTPD (N,N,N',N'-tetra(4-methoxyphenyl) )-benzidine); BP2T(5,5'-bis(biphenyl-4-yl)-2,2'-bithiophene); Di-NPB(N,N′-bis-[(1-naphthyl)-N,N′-diphenyl]-1,1′-biphenyl)-4,4′-diamine); α-NPB(N,N'-bis(naphthyl-1-yl)-N,N'-diphenylbenzidine); TNATA(4,4′,4″-tris-(N-(naphthyl-2-yl)-N-aniline)triphenylamine); BPAPF(9,9-bis[4-(N,N-bis-biphenyl-4-yl-amino)phenyl]-9H-fluorene); spiro-NPB(N2,N7-bis-1-naphthyl-N2, N7-diphenyl-9,9'-spiro[9H-fluorene]-2,7-diamine); 4P-TPD (4,4'-bis-(N,N-diphenylamino)-tetraphenyl); PEDOT:PSS; spiro-OMeTAD; inorganic hole transport compounds (e.g., oxides of nickel, vanadium, copper, or molybdenum; CuI, CuBr, CuSCN, Cu2O, CuO, or CIS; perovskite; amorphous silicon; p-type group IV semiconductors, p-type group III-V semiconductors, p-type group II-VI semiconductors, p-type group I-VII semiconductors, p-type group IV-VI semiconductors, p-type group V-VI semiconductors, and p-type group II-V semiconductors). Both inorganic and organic p-type semiconductor materials may be undoped or doped with dopants known in the art.

[0048] The first photovoltaic sub-cell may have a conventional structure, wherein the first sub-cell, comprising a perovskite light absorber material, is arranged such that the n-type region is adjacent to the second sub-cell. The photovoltaic device is preferably configured to be irradiated through the p-type region of the first sub-cell.

[0049] Alternatively, the first photovoltaic sub-cell may have an inverted structure, wherein the first sub-cell, comprising a perovskite light absorber material, is arranged such that the p-type region is adjacent to the second sub-cell. The photovoltaic device is preferably configured to be irradiated through the n-type region of the first sub-cell.

[0050] In such a configuration, it is further preferred that the metal (e.g., titanium) oxynitride layer is adjacent to and in contact with the semiconductor layer closer to the second sub-cell (i.e., a p-type semiconductor layer when the multi-junction device configuration is conventional, or an n-type semiconductor layer when the multi-junction device configuration is inverted).

[0051] In another preferred configuration, one of the n-type or p-type semiconductor layers of the first sub-cell is adjacent to and in contact with the main surface of a transparent conductive oxide layer, and the opposite main surface of this transparent conductive oxide layer is adjacent to and in contact with a titanium oxynitride layer. In such a configuration, the transparent conductive oxide layer can advantageously be used to protect the titanium oxynitride layer during the deposition of the first sub-cell. The material used for the transparent conductive oxide layer can be selected from transparent and translucent conductive oxides (TCOs) known in the art. Typically, the average transmittance of transparent materials will be about 100%, or 90% to 100%, while the average transmittance of translucent materials will typically be 10% to 90%, typically 40% to 60%. Examples include ITO (indium tin oxide), FTO (fluorine-doped tin oxide), or AZO (aluminum-doped tin oxide). The thickness of the transparent conductive oxide layer is preferably 1 nm to 25 nm, more preferably 5 nm to 22 nm, and more preferably 10 nm to 20 nm. However, it should be noted that the transparent conductive oxide layer is not mandatory and can be omitted, which can further simplify the manufacturing process and reduce costs. In this document, preferably, no transparent conductive oxide layer is provided except for the metal (e.g., titanium) nitride layer between the first and second sub-cell layers.

[0052] In a preferred embodiment, the second sub-cell is a silicon sub-cell. It preferably comprises a layer of crystalline silicon light absorber material. More preferably, the second sub-cell comprises a silicon heterojunction (SHJ). Alternatively, the second sub-cell may comprise other forms of silicon-based sub-cells (e.g., including diffused silicon junctions).

[0053] The term "silicon heterojunction" refers to an amorphous silicon / crystalline silicon heterojunction that uses a crystalline silicon (c-Si) wafer as a photoactive absorber and an amorphous silicon (a-Si) thin film for junction formation and surface passivation. In a preferred embodiment, the second sub-cell therefore includes a crystalline silicon layer sandwiched between two undoped amorphous silicon layers.

[0054] A silicon heterojunction (SHJ) is sometimes referred to as a heterojunction with an intrinsic thin layer (HIT) when any thin layer of intrinsic amorphous silicon (a-Si) is present as a passivation / buffer layer. Therefore, a silicon heterojunction (SHJ) typically comprises a p-type a-Si emitter, an intrinsic a-Si passivation / buffer layer, an n-type c-Si photoactive absorber, another intrinsic a-Si passivation / buffer layer, and a back field or front field (BSF or FSF) layer made of n-type a-Si. Optionally, a transparent conductive oxide (TCO) layer (e.g., ITO) may be included between the back field (BSF) layer and the back electrode in the silicon heterojunction (SHJ), which can promote maximization of infrared response by increasing the internal reflectivity at the back surface. SHJ cells can be illuminated via the p-side or the n-side. In the latter case, it can be referred to as a back junction solar cell. Therefore, SHJ cells can be combined with conventional or inverted perovskite cells to form a series cell.

[0055] In a preferred embodiment, an interconnect layer (i.e., an nc-Si:H layer) comprising doped nanocrystalline silicon may be provided between an undoped amorphous silicon layer and a metal (e.g., titanium) oxide nitride layer.

[0056] A preferred configuration of a multi-junction photovoltaic device according to the present invention includes (in the following order):

[0057] a) Front electrode;

[0058] b) A first sub-cell having a layer including a perovskite light absorber and a sub-cell comprising an n-type semiconductor layer and a p-type semiconductor layer, the n-type semiconductor layer being on one surface of the layer including the perovskite light absorber and the p-type semiconductor layer being on the other surface of the layer including the perovskite light absorber.

[0059] c) Optional transparent conductive oxide layer;

[0060] d) Metal nitride layer;

[0061] e) Optional doped amorphous silicon layer;

[0062] f) A second sub-cell, comprising a crystalline silicon light absorber material layer between a first undoped amorphous silicon layer and a second undoped amorphous silicon layer; and

[0063] g) Rear electrode.

[0064] Figure 2 and Figure 3 The image shows a specific example of a preferred device configuration for using this silicon heterojunction in the second sub-cell (i.e., the bottom cell).

[0065] Figure 2 A monolithically integrated multi-junction photovoltaic device 200 is schematically illustrated, comprising a first / top sub-cell 210, which includes a photoactive region comprising perovskite material, and a second / bottom sub-cell 220 comprising a photoactive silicon absorber. The multi-junction photovoltaic device 200 has a monolithically integrated structure and therefore includes only two electrodes, a front electrode 201 and a rear electrode 202, with the first sub-cell 210 and the second sub-cell 220 disposed between these two electrodes. Specifically, the first sub-cell 210 is in contact with the front electrode 201 and the second sub-cell 220 is in contact with the rear electrode 202. The monolithically integrated multi-junction photovoltaic device may also typically include a metal grid on the top surface of the front electrode 201 as top contacts (not shown). For example, a metal grid or fingers created by screen-printing a paste of silver and / or copper may be provided on the top contacts. Figure 2 In the example, the first sub-cell 210 has an inverted structure. Specifically, the first sub-cell 210 is arranged such that the p-type semiconductor layer 213 is adjacent to the second sub-cell 220. The photovoltaic device 200 is configured to be irradiated through the n-type semiconductor layer 212 of the first sub-cell 210. A photoactive region formed by the perovskite layer 211 is disposed between the p-type semiconductor layer 213 and the n-type semiconductor layer 212. Figure 2 The second sub-cell (bottom cell) 220 includes a silicon heterojunction (SHJ) with a crystalline silicon layer 221, in this example an n-type c-Si photoactive absorber, sandwiched between a first undoped amorphous silicon layer 222 and a second undoped amorphous silicon layer 224, serving as an intrinsic a-Si (i.e., a-Si(i)) passivation / buffer layer. Below the second undoped amorphous silicon layer 224, a p-type amorphous silicon (a-Si) layer 225 is formed adjacent to the back electrode 202. A titanium oxynitride layer 203 is necessaryly disposed between the first sub-cell 210 and the second sub-cell 220. Figure 2 As further shown in the preferred embodiment, a doped amorphous silicon layer 205 (i.e., n-doped) is disposed between the second sub-cell 220 and the titanium oxynitride layer 203. This layer serves to prevent sputtering damage to the first undoped amorphous silicon layer 222 (i.e., the a-Si(i) layer) and to provide good electron-selective contact with the second sub-cell 220. Furthermore, Figure 2 The structure includes a transparent conductive oxide (TCO) layer 204, which may be formed of ITO or the like, between the p-type region of the first sub-cell 210 and the titanium oxynitride layer 203. The TCO layer 204 can protect the stack from oxidation before the n-type region of the first sub-cell 210 is deposited. However, it should be understood that the presence of the transparent conductive oxide layer 204 and the doped amorphous silicon layer 205 is optional.

[0066] As described above, the multi-junction device according to the present invention may include a conventional configuration and an inverted configuration. Figure 3 An example of a conventional structure is shown in the figure. The multi-junction photovoltaic device 300 shown includes a front electrode 301 and a rear electrode 302, wherein a first sub-cell 310 and a second sub-cell 320 are disposed between the two electrodes. Specifically, the first sub-cell 310 is in contact with the front electrode 301 and the second sub-cell 320 is in contact with the rear electrode 302. The first sub-cell 310 is arranged such that an n-type semiconductor layer 312 is adjacent to the second sub-cell 320. The photovoltaic device 300 is configured to be irradiated through the p-type semiconductor layer 313 of the first sub-cell 310. A photoactive region formed by the perovskite layer 311 is disposed in the p-type semiconductor layer 313 and the n-type semiconductor layer 312. Figure 3 The second sub-cell (bottom cell) 320 includes a silicon heterojunction (SHJ), wherein a crystalline silicon layer 321 is sandwiched between a first undoped amorphous silicon layer 322 and a second undoped amorphous silicon layer 324, which serve as a passivation / buffer layer. Below the second undoped amorphous silicon layer 324, an n-type amorphous silicon (a-Si) layer 325 is formed adjacent to the rear electrode 302. A metal (e.g., titanium) oxide nitride layer 303 is disposed between the first sub-cell 310 and the second sub-cell 320. Furthermore, a doped amorphous silicon layer 305 (i.e., p-doped) is disposed between the second sub-cell 320 and the metal oxide nitride layer 303 to protect the first undoped amorphous silicon layer 322 (i.e., the a-Si(i) layer).

[0067] Generally, it should be understood that there are no particular limitations on the specific configuration of the first and second sub-cells, and each of them may include multiple sub-layers and one or more intermediate layers disposed between the first and second sub-cells. Furthermore, it should be noted that a monolithic integrated multi-junction photovoltaic device may include more than two sub-cells, as long as the individual sub-cells are connected in series between a pair of terminals. Examples of triple-sub-cell structures include, but are not limited to, bifacial monolithic integrated multi-junction photovoltaic devices comprising: a top sub-cell (second sub-cell) including a photoactive region comprising perovskite material; a middle sub-cell (first sub-cell) including a silicon heterojunction (SHJ); and a bottom sub-cell including a photoactive region comprising perovskite material.

[0068] Furthermore, those skilled in the art will understand that while the embodiments illustrated herein relate to photovoltaic devices with multi-junction structures, wherein the top perovskite sub-cell is shown as having a planar heterojunction arrangement, wherein a dense perovskite layer is disposed between a p-type material layer and an n-type material layer without openings, the interconnect layers described herein are equally applicable to multi-junction photovoltaic devices in which the top perovskite sub-cell has other configurations. For example, the top perovskite sub-cell may comprise a porous support of a semiconductor or dielectric material, on which the perovskite material is disposed as a thin layer or as a capping layer. As a further example, the top perovskite sub-cell may comprise only a charge transport region, as it has been shown that functional photovoltaic devices comprising photoactive perovskites can be formed without any hole transport material.

[0069] Manufacturing method

[0070] In a second embodiment, the present invention relates to a method for manufacturing a multi-junction photovoltaic device, the multi-junction photovoltaic device comprising a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material, the method comprising the step of depositing a metal (e.g., titanium) oxide nitride layer between the first sub-cell and the second sub-cell. In a preferred embodiment, the multi-junction photovoltaic device is the device described in conjunction with the first embodiment above.

[0071] More specifically, the method may include the following steps: providing a bottom sub-cell (i.e., a second sub-cell) on a rear electrode; depositing a metal (e.g., titanium) oxynitride layer on the bottom sub-cell; providing a top sub-cell (i.e., a first sub-cell) having a layer comprising a perovskite light absorber material on the metal (e.g., titanium) oxynitride layer; and providing a front electrode on the top sub-cell.

[0072] It should be understood that there are no particular limitations on the steps of setting the first and second sub-cells, as well as the front and rear electrodes, and those skilled in the art can appropriately select from various techniques according to the properties of each (sub)layer. Typical techniques include, but are not limited to, solution deposition techniques (e.g., by screen printing, blade coating, slotted dye coating, spin coating, etc.), sol-gel methods, vapor deposition (e.g., physical vapor deposition (PVD), plasma-enhanced chemical vapor deposition (PECVD)), sputtering deposition, pulsed laser deposition, vacuum deposition, electroplating, etc. However, for simplicity and equipment cost, PECVD methods are preferably avoided to fully utilize the advantages of the present invention.

[0073] In a preferred embodiment of the invention, the metal (e.g., titanium) oxide layer is deposited by physical vapor deposition (PVD), preferably by sputtering deposition, and particularly preferably by magnetron sputtering, which does not require complex equipment and allows for rapid deposition with consistent results.

[0074] In a further preferred embodiment, TiO x N y The layer can be deposited using a magnetron sputtering system employing a titanium nitride (TiN) target and an Ar / O2 mixed gas, which allows for fine-tuning of the TiO2 layer by simply changing the oxygen flow rate. x N y Optical and electrical properties of the thin film. Sputtering power, frequency, and base pressure are not particularly limited and can be appropriately adjusted by a technician. F. Chen et al., Optical Materials Express 2014, 4(9) 1833-1847 discloses adjusting magnetron sputtering conditions to provide TiO₂ with suitable optical and electrical properties. x N y An exemplary method for layers.

[0075] By using sputtering technology, deposition rates of 0.4 nm / s or higher, such as 0.6 nm / s or higher, or 0.8 nm / s or higher, for titanium oxynitride layers can be achieved, where each value refers to the average thickness of the titanium oxynitride layer. Therefore, intermediate layers can be deposited at significantly higher rates compared to dedicated PECVD techniques used in the art.

[0076] It should be understood that the preferred features of the first and second embodiments can be freely combined in any combination, except for combinations in which at least some features are mutually exclusive.

[0077] Once the above disclosure is given, many other features, modifications, and improvements will become apparent to those skilled in the art.

[0078] Example

[0079] The present invention is illustrated by the following examples.

[0080] Example 1:

[0081] If the refractive index n of the interlayer material IL The refractive index is between that of perovskite and silicon materials (n PVSK <n IL <n Silicon The solar-to-electrical-energy conversion efficiency (PCE) of perovskite / silicon tandem solar cells can be improved by placing a sandwich layer between the two absorber layers. By doing so, such a layer reduces the reflection of infrared light occurring at the interface region between the two absorbers. To maximize this beneficial effect, the sandwich layer should have a refractive index (n) of approximately 2.7 at a wavelength of 800 nm. IL,800=2.7) and a thickness of approximately 100 nm. This most effectively utilizes the interference effect between light incident on the upper and lower interfaces of the interlayer. It has been shown that doped nanocrystalline silicon oxide (nc-SiOx) can be used very effectively as such an interlayer because it can be fabricated to possess optoelectronic properties, thus utilizing optical effects without degrading electrical performance due to, for example, additional series resistance losses. However, the complex fabrication method (PECVD) and the relatively slow nc-SiOx deposition rate have prompted the search for alternative materials that can be produced more easily. According to the above invention, sputtered TiO2 has been fabricated. x N y Sandwich-type perovskite / silicon tandem solar cells. Current results indicate that the optimal refractive index n of the thin film at 800 nm wavelength is... 800 It is approximately 2.4 (TiO) x N y Maximum achievable refractive index n 800 (Approximately 2.5). Due to the lower maximum refractive index, the optical enhancement is expected to be slightly lower compared to existing nc-SiOx technologies.

[0082] method

[0083] TiO with a thickness of 100 nm x N y A layer is deposited on top of a set of silicon heterojunction (SHJ) solar cells, which are fabricated together with a set of SHJ reference (control) cells without specific optical interlayers. SHJ cell fabrication and TiO2 x N y The deposition was based on Chen et al., “Control of optical properties of TiN”. x O y The method described in “Films and Application for High Performance Solar Selective Absorbing Coatings”, Vol. 4, 9, 1833-1847, (2014) was used. To avoid problems related to electrical contact, the layer was sandwiched between 20 nm thick TCO layers. Figure 7 The device stack is shown in the image. Due to its thinness, the optical impact of the additional TCO layer is relatively small.

[0084] According to the prior art method described in Al-Ashouri et al., “Monolithic perovskite / silicon tandem solar cell with >29% efficiency by enhanced hole extraction”, Vol. 370, 6522, 1300-1309, (2020), a perovskite top cell was deposited. The tandem cell was then characterized by current-voltage (IV) measurements under illumination, thereby carefully and appropriately simulating the AM1.5G standard solar spectrum. Figure 8 Representative IV measurements are shown in the figure. Furthermore, external quantum efficiency measurements are performed using bias light to independently measure each sub-cell. Optical simulations are conducted. The optical properties of the thin film are measured using spectral ellipsometry. Figure 9 An example of the extracted refractive index and absorption or extinction coefficient "nk" is shown in the figure. Optical simulations are performed using the transfer matrix method. The results of the optical simulations are displayed in the supporting information (see [link]). Figure 10 and Figure 11 ).

[0085] Results and Discussion

[0086] Figure 4 The changes (increments) in IV characteristics for a total of six series-connected cells are shown: power conversion efficiency (PCE), short-circuit current density (Jsc), and open-circuit voltage (V). OC ) and fill factor (FF), three series cells from "no sandwich separator", three series cells from "TiO" x N y "Separation". For each of the four parameters, the results are normalized to the average of "no mezzanine separation" to account for the differences.

[0087] Figure 4 The image also shows box plots for each distribution. For TiO₂... x N y Separating the values, the average PCE is slightly lower—this is due to the change in the average FF. On the other hand, an increase in the average Jsc can be observed. +0.2-+0.3mA / cm 2The ΔJsc is much lower than another nc-SiOx reference, namely Mazzarella et al. “Infrared Light Management Using a Nanocrystalline Silicon Oxide Interlayer in Monolithic Perovskite / Silicon Heterojunction Tandem Solar Cells with Efficiency above 25%”, Advanced Energy Materials, Vol. 9, 14, (2019), where +1.8 mA / cm² can be observed. 2 The gain (also relatively) Figure 11 In addition, the average Voc increased slightly.

[0088] Figure 5 The measured quantum efficiency from two representative cells for each separator is shown. An interference effect can be observed in the EQE of the silicon-bottom cell. It has been shown that this interference effect is caused by light reflected at the interface region (Mazzarella et al. Advanced Energy Materials, Vol. 9, Issue 14, 11 April 2019). Furthermore, it can be seen that the amplitude of the interference fringes is reduced in the EQE of the cell with the sandwich layer. The experimentally observed EQE curves are compared with the simulated EQE curves (…). Figure 10 A comparison reveals similar behavior, where the amplitude of the interference fringes decreases. Although the locations of the maximum and minimum values ​​of the interference fringes are not exactly the same, this is likely due to a slight difference in the thickness of the perovskite absorber between the experimental and simulated results.

[0089] Figure 6 This demonstrates the application of this technology to three cells without sandwich panels and three cells with TiO₂. x N y The EQE curves of the sandwiched cell and the Jsc values ​​of the perovskite sub-cell and silicon sub-cell calculated using the AM1.5G standard solar spectrum, respectively, show that the bottom cell is composed of TiO2. x N y The benefit in the interlayer is approximately 0.3 mA / cm. 2 The gain was not as high as theoretically predicted (compared to...). Figure 11 This could be because the refractive index on the battery is slightly different from that measured on the glass substrate. Alternatively, the additional contact layer omitted in the simulation may have a larger effect than initially expected.

[0090] In addition, Figure 6As can be seen, in all cases, the Jsc value of the perovskite sub-cell is greater than that of the silicon sub-cell. Since the Jsc of the series-connected device is limited by the Jsc of the cell with the lower current density (due to the monolithic series connection), therefore... Figure 4 The visible Jsc gain can be explained by limiting the increase in Jsc in the sub-cell. Therefore, we can infer that the EQE and IV measurements are very consistent. Somewhat surprisingly, there is a decrease in Jsc in the perovskite sub-cell. According to simulations, a small change can be expected because less light is reflected back to the top cell. However, the magnitude of this change should be much smaller than the gain in the silicon bottom sub-cell. Since the change in the Jsc group of the "no sandwich" perovskite sub-cell is the largest of the four Jsc groups, this unexpectedly large decrease is likely caused by factors unrelated to the experiment, such as measurement errors or process variations in one of the top cell processes. Figure 5 The difference in the top cell EQE near the 400nm wavelength visible in the image supports this hypothesis, as it is not visible in theoretical predictions (comparison). Figure 10 Light with a wavelength of 400nm should not be able to "see" the interlayer, but should be completely absorbed by the top cell.

[0091] in conclusion

[0092] In conclusion, the above results regarding series-connected cells confirm the theoretical predictions, namely, the use of TiO2. x N y The sandwich structure reduces the reflection loss of perovskite / silicon tandem cells by 0.3 mA / cm² in the infrared range of the spectrum. 2 The equivalent weight.

[0093] Figure Labels

[0094] 100 / 200 / 300: Single-cell multi-junction photovoltaic equipment

[0095] 110 / 210 / 310: First sub-cell

[0096] 120 / 220 / 320: Second sub-cell

[0097] 101 / 201 / 301: Front electrode

[0098] 102 / 202 / 302: Rear Electrode

[0099] 103 / 203 / 303: Metallic (e.g., titanium) oxide layer

[0100] 204: Transparent conductive oxide layer

[0101] 205: Doped amorphous silicon layer (n-type)

[0102] 305: Doped amorphous silicon layer (p-type)

[0103] 211: Perovskite layer

[0104] 212 / 312: n-type semiconductor layer

[0105] 213 / 313: p-type semiconductor layer

[0106] 221 / 321: Crystalline silicon layer

[0107] 222 / 322: First undoped amorphous silicon layer

[0108] 224 / 324: Second undoped amorphous silicon layer

[0109] 225: Doped amorphous silicon layer (p-type)

[0110] 325: Doped amorphous silicon layer (n-type)

Claims

1. A multi-junction photovoltaic device, comprising a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material, characterized in that, A metal nitride layer is disposed between the first sub-cell and the second sub-cell, wherein the metal in the metal nitride layer is an early transition metal selected from: Ti, W, Mo, Hf, Ta, Nb, Zr, Cr and V.

2. The multi-junction photovoltaic device according to claim 1, which has a monolithic integrated structure.

3. The multi-junction photovoltaic device according to claim 2, wherein, The device has a series structure.

4. The multi-junction photovoltaic device according to claim 1 or 2, wherein, The metal is Ti.

5. The multi-junction photovoltaic device according to claim 1 or 2, wherein, The first sub-cell also includes an n-type semiconductor layer and a p-type semiconductor layer on both sides of the layer comprising the perovskite light absorber material.

6. The multi-junction photovoltaic device according to claim 5, wherein, The oxynitride layer is adjacent to and in contact with the n-type semiconductor layer or the p-type semiconductor layer.

7. The multi-junction photovoltaic device according to claim 5, wherein, One of the n-type semiconductor layer or the p-type semiconductor layer is adjacent to and in contact with the main surface of a light-transmitting conductive oxide layer, and the opposite main surface of the light-transmitting conductive oxide layer is adjacent to and in contact with the metal nitride layer.

8. The multi-junction photovoltaic device according to claim 1 or 2, wherein, The second sub-cell includes a layer of crystalline silicon light absorber material.

9. The multi-junction photovoltaic device according to claim 8, wherein, The second sub-cell includes a heterojunction photovoltaic device.

10. The multi-junction photovoltaic device according to claim 9, wherein, The second sub-cell includes a crystalline silicon layer sandwiched between two undoped amorphous silicon layers.

11. The multi-junction photovoltaic device according to claim 10, wherein, A layer comprising doped amorphous silicon is disposed between the undoped amorphous silicon layer and the metal oxide nitride layer.

12. The multi-junction photovoltaic device according to claim 10, wherein, The metal oxide nitride layer is a titanium nitride layer, and a layer including doped nanocrystalline silicon oxide is disposed between the undoped amorphous silicon layer and the titanium nitride layer.

13. The multi-junction photovoltaic device according to claim 1, comprising, in the following order: a) Front electrode; b) The first sub-cell has a layer including a perovskite light absorber and includes a sub-cell comprising an n-type semiconductor layer and a p-type semiconductor layer, the n-type semiconductor layer being on one surface of the layer including the perovskite light absorber and the p-type semiconductor layer being on the other surface of the layer including the perovskite light absorber. c) The metal nitride layer; d) Doped amorphous silicon layer; e) The second sub-cell, comprising a crystalline silicon light absorber material layer between a first undoped amorphous silicon layer and a second undoped amorphous silicon layer; and f) Rear electrode.

14. The multi-junction photovoltaic device according to claim 13, wherein, The device also includes a light-transmitting conductive oxide layer between layers b) and c).

15. The multi-junction photovoltaic device according to claim 13, in, The p-type semiconductor layer of the first sub-cell is adjacent to the metal nitride layer; Wherein, the doped amorphous silicon layer is an n-type amorphous silicon layer; and The second sub-cell also includes a p-type amorphous silicon layer adjacent to the rear electrode.

16. The multi-junction photovoltaic device according to claim 14, wherein, The p-type semiconductor layer of the first sub-cell is adjacent to the light-transmitting conductive oxide layer; Wherein, the doped amorphous silicon layer is an n-type amorphous silicon layer; and The second sub-cell also includes a p-type amorphous silicon layer adjacent to the rear electrode.

17. The multi-junction photovoltaic device according to claim 1 or 2, wherein, The metal nitride layer is suitable for having a refractive index between 2.3 and 3.

7.

18. The multi-junction photovoltaic device according to claim 1 or 2, wherein, The metal nitride layer is suitable for having a refractive index between 2.3 and 2.

9.

19. The multi-junction photovoltaic device according to claim 12, wherein, The titanium oxynitride layer is suitable to have a refractive index between 2.3 and 3.

7.

20. The multi-junction photovoltaic device according to claim 12, wherein, The titanium oxynitride layer is suitable to have a refractive index between 2.3 and 2.

9.

21. The multi-junction photovoltaic device according to claim 1 or 2, wherein, The metal nitride layer has a thickness between 20 nm and 200 nm.

22. A method of manufacturing a multi-junction photovoltaic device, the multi-junction photovoltaic device comprising a first sub-cell and a second sub-cell, the first sub-cell having a layer comprising a perovskite light absorber material, the method comprising the step of depositing a metal nitride layer between the first sub-cell and the second sub-cell, wherein the metal in the metal nitride layer is an early transition metal selected from: Ti, W, Mo, Hf, Ta, Nb, Zr, Cr and V.

23. The method for manufacturing a multi-junction photovoltaic device according to claim 22, wherein, The metal nitride layer is deposited using physical vapor deposition.

24. The method for manufacturing a multi-junction photovoltaic device according to claim 23, wherein, The metal oxynitride layer is a titanium oxynitride layer.

25. The method for manufacturing a multi-junction photovoltaic device according to claim 23, wherein, The metal oxynitride layer is a titanium oxynitride layer, and the deposition rate of the titanium oxynitride layer is 0.4 nm / s or higher.

26. The method for manufacturing a multi-junction photovoltaic device according to claim 23 or 25, wherein, The metal oxide layer is deposited by sputtering deposition.

Citation Information

Patent Citations

  • Optoelectronic devices with organometal perovskites with mixed anions

    WO2013171517A1

  • Optoelectronic device

    WO2014045021A1

  • Multijunction photovoltaic device

    WO2016198898A1

  • Spray cap for aerosols

    WO2018015203A1

  • Multijunction photovoltaic device

    WO2018150203A1